Perbandingan Expected Return dan Actual Return Portofolio Saham Optimal dengan Menggunakan Single Index Model Pada Saham yang Terdaftar di Jakarta Islamic Index (JII) - Ruzi, Fahrul (Jurnal Profiet, 2025)
This study aims to compare the performance of expected returns and actual returns of stock portfolios formed using the single index model method on stocks included in the Jakarta Islamic Index (JII). In addition, this study will also compare the actual returns of stock portfolios against the JII index and the Composite Stock Price Index (IHSG). The results of the study show that the stocks selected in the portfolio are TPIA (26.21%), AKRA (20.53%), ADMR (10.55%), BRIS (21.45%), ITMG (9.52%) and BRPT (11.72%) with an expected portfolio return of 3.23% and a stock portfolio risk of 8.73%. This stock portfolio generated an actual return of 2.0%. This result is smaller when compared to the expected portfolio return, but this result is better when compared to the performance of the JII which fell by 13.22% and the IHSG which fell by 1.37%. Thus, it can be concluded that the performance of the stock portfolio formed with a single index model on stocks included in the Jakarta Islamic Index can provide better actual returns when compared to the JII and IHSG. Keywords: Single Index Model, Portfolio, Return, IHSG, Jakarta Islamic Index